The effect of PAMAM dendrimers on mesenchymal stem cell viability and differentiation - Gonçalves, M. (2019)
Stem cells and nanomaterials are two new and exciting fields of science that are evolving very fast and that are starting to establish ties. Nanomaterials should, however, be designed to interact with stem cells without compromising their biological characteristics, in other words, without affecting their viability and differentiation potential. In the present report and for the first time, the effects of poly(amidoamine) (PAMAM) dendrimers on the viability and differentiation ability towards the osteogenic and adipogenic lineages of human mesenchymal stem cells (hMSCs) are systematically evaluated. Studies were done as a function of the cell culture media composition and PAMAM dendrimer surface functionalization, generation, and concentration. hMSCs were exposed to amino and hydroxyl (generations 2, 4 and 6), and carboxylate (generations 1.5, 3.5 and 5.5) functionalized dendrimers, at two different concentrations (10 μg/mL and 0.5 μg/mL), for a period of 21 days. Overall, the results revealed that amino functionalized dendrimers can be severely cytotoxic, the extension of cell death being dependent on the concentration of amino groups in solution. However, in all cases, the differentiation of hMSCs towards the osteogenic and adipogenic phenotypes seems not to be affected as demonstrated by staining in in vitro cultures.